Examining Students’ Perceptions of an Smalltalk2Me Powered Conversation Assistant in the Speaking Class - Ita Permatasari; Rizka Maulina Wulandari; Dian Palupi; Halim Ahmad Faizin; Bima Pramudya Waskito Adji (International Forum of Researchers and Lecturers, 2025)
This study investigates students’ perceptions of Smalltalk2Me, an artificial intelligence (AI)-powered conversational assistant designed to improve speaking skills in classroom learning. The main objective of this research is to explore how students perceive the tool’s effectiveness, usefulness, interactivity, and overall learning experience when using it for speaking practice. The research employed a qualitative descriptive method, with data collected through semi-structured interviews involving students who had used Smalltalk2Me as part of their English-speaking activities. The interview data were analyzed thematically to identify emerging patterns related to engagement, motivation, and skill development. The findings reveal that students view Smalltalk2Me as an effective and accessible tool that enhances speaking fluency and confidence since it allows practice anytime and anywhere. Students also appreciate its realistic conversation simulations and personalized feedback, which help them recognize pronunciation errors, improve vocabulary use, and refine sentence structure. Additionally, the AI assistant creates a supportive and low-anxiety learning environment, making learners more comfortable expressing themselves in English. Overall, the study concludes that Smalltalk2Me serves as a valuable supplementary tool for improving students’ speaking competence and fostering autonomous learning in technology-enhanced language classrooms.